Implementasi metode regresi dalam pengolahan data platfrom rotten tomatoes movies - Muafiyah, Hanik; Sholihah, Riza Mar’atus (Maliki Interdisciplinary Journal, 2025)
This research aims to implement the linear regression method in analyzing data from the Rotten Tomatoes Movies platform, which provides global film information including critic ratings, duration and audience scores. The multiple linear regression method is applied to analyze the influence of independent variables, namely film duration and critic rating (tomatoMeter), on the dependent variable, namely audience score (audienceScore). The results of the analysis show that these two independent variables have a significant influence on audience scores, with a coefficient of determination (R²) of 23.51%, which means that 23.51% of the variation in audience scores can be explained by duration and critic ratings. The regression model obtained is with (audience score), (film duration), (critic rating). However, the relatively low R² value indicates the presence of other variables that may influence viewer scores. This study illustrates the potential of linear regression in processing big data in the film industry for prediction purposes, and indicates the importance of additional variables to improve the accuracy of audience score prediction models.